Industrial Planning and Licensing Policy Final Report - Planning Commission (Planning Commission, Government of India, 1969)
The Industrial Planning and Licensing Policy Final Report by R.K. Hazari presents a critical evaluation of India’s industrial licensing framework under the Industries (Development and Regulation) Act of 1951, examining its effectiveness between 1959 and 1966 in guiding planned industrial growth. The report assesses the licensing system against its core objectives—regulating development in line with national priorities, preventing monopolistic concentration, safeguarding small-scale industries, promoting entrepreneurship, ensuring balanced regional distribution, and fostering technological advancement. Analysis of 5,598 industrial license applications reveals significant concentration of investment approvals among a few dominant industrial houses, heavy reliance on imported capital goods, and limited success in dispersing industry to underdeveloped regions. States such as Maharashtra and West Bengal captured a disproportionate share of approved investments, while others like Jammu & Kashmir and Orissa lagged considerably, underscoring persistent regional imbalances. The findings suggest that the licensing mechanism often reinforced established industrial interests and created barriers to new entrants rather than effectively channelizing investment. The report recommends raising licensing exemption limits, introducing rigorous feasibility assessments, defining clearer sectoral priorities, strengthening support for small and medium enterprises, and instituting stronger follow-up mechanisms to ensure timely project implementation. Overall, the study advocates a shift toward a more transparent, flexible, and development-oriented industrial policy framework capable of promoting equitable growth, enhancing competition, and aligning industrial expansion with evolving economic objectives.
Government of India Planning Commission
Keywords: Industrial Planning and Licensing Policy; R.K. Hazari Report; Industries Development and Regulation Act 1951; Industrial Licensing System; Regional Industrial Disparities; Investment Approvals 1959-1966; Monopoly Concentration; Small Scale Industry Protection; Foreign Investment Participation; Industrial House Dominance; Manufacturing Sector Growth; Policy Reform Recommendations